1981
DOI: 10.1002/1097-0142(19810315)47:6<1262::aid-cncr2820470606>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy of malignant melanomas: An evaluation of clinically used fractionation schemes

Abstract: To assess the importance of radiation dose fraction size in the treatment of malignant melanomas, the records of 48 patients (83 sites) treated at Tufts-New England Medical Center from 1971 to 1979 have been retrospectively reviewed. During this period, the dose fractionation schemes evolved from standard fraction size to large-dose techniques. Radiation fraction size was observed to be the major factor in the clinical response of melanoma. Fractions of 600-800 rad resulted in the best overall response (80%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

1982
1982
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(15 citation statements)
references
References 10 publications
0
11
0
4
Order By: Relevance
“…Adjuvant radiotherapy was not prescribed for our patient because of a paucity of evidence to suggest any benefit. 2,10,49 Primary melanocytic neoplasms of the CNS consist of a spectrum ranging from well-differentiated melanocytomas to melanoma. Recently, Brat et al 50 studied the clinicopathologic features of 33 cases and found a clear distinction between melanocytoma and melanoma by histologic and immunohistochemical criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiotherapy was not prescribed for our patient because of a paucity of evidence to suggest any benefit. 2,10,49 Primary melanocytic neoplasms of the CNS consist of a spectrum ranging from well-differentiated melanocytomas to melanoma. Recently, Brat et al 50 studied the clinicopathologic features of 33 cases and found a clear distinction between melanocytoma and melanoma by histologic and immunohistochemical criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Overgaard et al [42] showed a statistically significant difference in CR (57% vs 24%) for fractional dose greater than or equal to 4 Gy compared to less than 4 Gy. Other investigators [43,44] have reported similar results. The toxicity of such treatments has been limited with no grade 3 toxicity in one report [35].…”
Section: Dose and Fractionationmentioning
confidence: 99%
“…unbekannte Regionen 14 (12%). Die Histologie bei Primärdia-gnose war nodulär (NM) bei 51 (47%), superfiziell spreitend (SSM) bei 35 (25) 3 (27) 17 (30) 10 (19) n. s. Lokalrezidiv (in-field) 2 ( 7) 2 (18) Lokale Lymphknotenmetastase 8 ( 7) 5 ( 9) 3 ( 6) Regionale In-transit-Metastase (M1a) 9 ( 7) 1 ( 9) 6 (11) 2 ( 4) n. s. Fernmetastasen (M1b) 11 ( 9) 6 (11) 5 ( 9) Rezidiv/Progression (Jahre) MW ± SD 2,5 ± 2,1 4,6 ± 3,2 3,3 ± 3,9 0,6 ± 0,8 p < 0,05 Table 4. Initial and long-term response and UICC stage prior to RT start (n. s. = not significant; NED = no evidence of disease).…”
Section: Patienten-und Tumorparameterunclassified
“…Radiobiologische und klinische Daten [22,23,25,35] weisen bei hypofraktionierter Radiotherapie und großen Einzeldosen bessere Ansprechraten auf als bei konventioneller Radiotherapie; dem widersprechen mono- [13,23] und multizentrische Studien [32]. In unserer Studie war die Gesamtstrahlendosis univariat ein Prognosefaktor, multivariat blieb dies unbestätigt.…”
Section: Patienten-und Tumorparameterunclassified
See 1 more Smart Citation